Adipose-Specific Deletion of TFAM Increases Mitochondrial Oxidation and Protects Mice against Obesity and Insulin Resistance - Vernochet, Cecile (2012)
Obesity and type 2 diabetes are associated with mitochondrial dysfunction in adipose tissue, but the role for adipose tissues mitochondria in the development of these disorders is currently unknown. To understand the impact of adipose tissue mitochondria on whole body metabolism, we have generated a mouse model with disruption of the mitochondrial transcription factor A (TFAM) specifically in fat. F-TFKO adipose tissue exhibit decreased mtDNA copy number, altered levels of proteins of the electron transport chain, and perturbed mitochondrial function with decreased Complex I activity and greater oxygen consumption and uncoupling. As a result, F-TFKO mice exhibit higher energy expenditure and are protected from age- and diet-induced obesity, insulin resistance and hepatosteatosis, despite a greater food intake. Thus, TFAM deletion in the adipose tissue increases mitochondrial oxidation that has positive metabolic effects suggesting that regulation of adipose tissue mitochondria may be a potential therapeutic target for the treatment of obesity.